Development of Web-Based Learning Media with an Inquiry Model to Enhance Learning Outcomes and Student Independence in Elementary Schools - Rosbina, Atania; Wardani, Sri; Haryono, Haryono (Journal of Innovation and Research in Primary Education, 2025)
This study aimed to develop a web-based learning medium utilizing an inquiry model to enhance primary school students' cognitive learning outcomes and learning independence. The development procedure followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 60 fifth-grade elementary school students, divided into experimental and control groups. Data collection techniques included observation, questionnaires, and learning achievement tests. Media validity assessments by material and media experts yielded an average score of 94% ("very valid" category), while practitioner teacher evaluations indicated 91% feasibility. Effectiveness tests revealed significant improvements in the experimental group: average cognitive learning outcomes increased from 68.4 to 87.2, whereas the control group only rose from 66.1 to 72.3. Similarly, the experimental group's learning independence questionnaire scores increased from 66.5 to 85.6, compared to the control group's increase from 67.2 to 70.8. T-tests confirmed the significance of these improvements (p<0.05) for both variables. The main innovation lies in integrating the inquiry model into an interactive web-based medium specifically designed for the IPAS topic "Earth Layer Structure." This medium empowers students to construct knowledge through self-exploration, visual interaction, and reflective, inquiry-based activities, addressing a gap in digital learning development at the primary school level. Practical implications suggest that this inquiry-based interactive web medium can serve as a strategic alternative for IPAS learning, emphasizing conceptual understanding and fostering learning independence. The medium's flexibility allows for broad integration into various learning scenarios, supporting both offline and online adaptive and personalized instruction.